BUKU TEKS BAHASA INDONESIA SMP DAN SMA KURIKULUM 2013 TERBITAN KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN 2014 - Fadilah, Rohana (Universitas Negeri Surabaya, 2015)
Text book is one of important instruments in successful learning. Ministry of Education and Culture published standard textbook. Readability’s textbook must compatible with student’s capability and psychology. Fry’s graph is the best readability measuring tool for textbook. Aim of this research is to descibe readability’s Indonesian textbooks of Junior and Senior High School curriculum 2013 published by Ministry of Education and Cultural 2014. The kind of this research is literature study. The data collection used documentation technique. The result of this reseach is (1) the readability of Indonesian textbook for seventh grader is not suitable for target student because 20 of 33 texts is not suitable for seventh grader student based on Fry’s graph, (2) the readability of Indonesian textbook for eighth grader is suitable for target student because 17 of 22 texts is suitable for eighth grader student based on Fry’s graph, (3) the readability of Indonesian textbook for tenth grader is not suitable for target student because 18 of 23 texts is not suitable for tenth grader student based on Fry’s graph, (4) the readability of Indonesian textbook for eleventh grader first semester is not suitable for target student because 9 of 10 texts is not suitable for eleventh grader student based on Fry’s graph, and (5) the readability of Indonesian textbook for eleventh grader second semester curriculum 2013 is not suitable for target student because 14 of 22 texts is not suitable for seventh grader student based on Fry’s graph.